Peran Pendidikan Jasmani Dalam Membangun Karakter Siswa SMP YP PGRI 4 Makassar - Tri Anggriawan; Ariana Asri; Hamsi Samir (Phsyical Education Health and Recreation Department of STKIP-YPUP Makassar, 2021)
This research is a qualitative research that aims to determine the role of physical education in building the character of cooperation, discipline and responsibility of the students of SMP YP PGRI 4 Makassar. The subjects in this study were students in grades VII, VIII, IX and two physical education teachers at SMP YP PGRI 4 Makassar. The instruments used in this study were the researchers themselves as the main instrument, observation sheets and interview guidelines. The stages of data analysis in this study are observational data analysis, interviews using qualitative descriptive analysis with data reduction, data presentation and drawing conclusions. The results of this study indicate that, the form of the discipline character of the students of SMP YP PGRI 4 Makassar, namely being present on time and wearing sports uniforms, the form of the character of student cooperation, namely helping each other among group members, the form of the character of responsibility of the students of SMP YP PGRI 4 Makassar when students do sports game